The Role of Islamic Education K.H. Asnawi in Social Changes in Banten Society, 1870-1945 - Amalia Dwi Sahara; Lina Herlina; Rilva Deni Yogatama; Muhammad Anggie Farizqi Prasadana (Institute of Research and Community Service UIN Prof. K.H. Saifuddin Zuhri, 2022)
This study aims to describe the role of Islamic education in the style of Kiai Haji (K.H.) Asnawi in the social changes of Banten society in 1870-1945, where the focus of the discussion is to compare people's lives before and after getting the influence of Islamic education from K.H. Asnawi. This study also seeks to provide theoretical benefits in the form of knowledge contributions regarding the history of education in Banten and practical benefits by making readers aware of the importance of Islamic education for the people of Banten. This research used historical methods consisting of topic selection, source collection, source criticism, interpretation, and writing. The results showed that the Islamic education of K.H. Asnawi positively impacted the people of Banten in the form of religious life following the Qadiriyahwa Naqsabandiyah Order and encouraging resistance to the Dutch